PENINGKATAN MOTIVASI BELAJAR DAN HASIL BELAJAR LAS LANJUT DENGAN MENERAPKAN METODE PROJECT- BASED LEARNING - Nurcholish Arifin Handoyono; Rabiman Rabiman (Universitas Sarjanawiyata Tamansiswa, 2017)
The objective of this research is to find: (1) implementation of project-based learning method in the advanced welding subject, (2) increased learning motivation by appling the project-based learning method, and (3) increased learning outcomes by appling the project-based learning method. This research uses classroom action research with three cycles, each cycle consists of four phases: planing, action, observe, and reflecting. Data were analyzed decriptively. The research results are as follows: (1) implementation of project-based learning method in the first cycle of 12.60 (65.00%) categorized as low, the second cycle of 15.92 (71.67%) categorized as high, and the third cycle of 16.77 (78.75%) categorized as very high, has increased by 3.32 (6.67%) from the first cycle to second cycle and by 0.85 (7.08%) from the second cycle to third cycle; (2) learning motivation in the first cycle of 12.60 categorized as high, the second cycle of 15.92 categorized as very high, and the third cycle of 16.77 categorized as very high, has increased by 3.32 from the first cycle to the second cycle and by 0.85 from the second cycle to third cycle; and (3) learning outcomes in the first cycle of 69.83 (B), the second cycle of 74.97 (B), and the third cycle of 84.85 (A-), has increased by 5.14 from the first cycle to the second cycle and by 9.88 of the second cycle to the third cycle.